Factors Influencing Purchase Behavior: Consumer Interest, Price, and Product Quality (Literature Review HRM) - Isbahi, Muhammad Baiqun (Danadyaksa: Post Modern Economy Journal, 2023)
Previous scientific studies or articles play a crucial role in the development of theories and understanding of phenomena, as they provide valuable support and reinforcement to the variables under investigation in the forthcoming research or scientific article. This scientific study aims to critically examine the various aspects that have been identified in consumer behavior literature as influential in shaping purchase behavior. Specifically, the factors of consumer interest, price, and product quality will be analyzed and discussed. The objective of composing this article is to establish a hypothesis regarding the potential influence of variables, which will then be employed in further research endeavors. The findings of this literature review paper are presented as follows: There are three main factors that drive consumer purchase behavior: consumer interest, price, and product quality.